A Statistical study on J&G Manufacturing Corporation - Borjal, Vera Adelle M.; Papio, Marivic A.; Tabucal, Natasha P. (Diliman, Quezon City College of Engineering, 2001)
J & G Engineering Fabric Corporation, in a joint venture with Karl Fischer of Germany, specializes in the manufacture of engineering fabrics. Acquisition of the intended weight of the engineering fabric is the most vital aspect to consider in the manufacturing processes involved in operations. It is essential that processes be controlled to avoid departure from the weight standards. This paper presents a study on the causes of the unwanted deviation from the desired fabric weight. Several machine and process parameter factors are studied for their response on engineering fabric weight. The factors that stand out in the said study are as follows : Spin Pump, Spinerette Temperature, Line Speed, and Spinerette Pressure. Investigation and experimentation is performed using the Design of Experiments (DOE). This explains and shows how important setting a parameter combination is, to achieve high quality output. Statistical techniques that are used to achieve the objective the team are Goodness of Fit Test, 2 Factorial Design, Multiple Linear Regression and Residual Plotting. Based on the results, the parameters Spin Pump and Spinerette Pressure greatly influence the fabric weight problem. The findings significantly are predicted to reduce the discrepancy of the weight output from the standard one. The recommendations of the team that the company use the linear equation model to determine the values for the Spin Pump and Spinerette Pressure in order to achieve the desired output.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics